Edukasi Pasien untuk Mengurangi Ketidaknyamanan Pasca Ekstubasi Endotracheal Tube General Anestesi - Aldi Hartono, Mochamad; Setyawati, Martyarini Budi; Handayani, Rahmaya Nova (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction: General anesthesia with endotracheal intubation frequently results in post-extubation discomfort manifested as sore throat, hoarseness, and respiratory distress due to airway trauma. Non-pharmacological education is essential to enhance patients’ understanding in minimizing these complaints. Objective: This community service activity aims to provide information and improve patients’ knowledge regarding the management of discomfort following ETT extubation. Methods: The activity commenced with participant identification, informed consent, and coordination with healthcare personnel. Thirty participants who underwent general anesthesia with ETT took part in this program. The activity employed an educational approach through interactive lectures and demonstrations to facilitate a deeper understanding of the material. Education was delivered for approximately 10 minutes using brochures and videos, beginning with a pre-test and concluding with a post-test. Evaluation was conducted using a questionnaire to measure the effectiveness of the educational intervention in enhancing patients’ knowledge after extubation. Results: The findings demonstrated an improvement in participants’ knowledge, wherein prior to the education, all participants (100%) had limited understanding, while after the intervention, the majority (25 participants; 83.3%) exhibited very good knowledge. The educational intervention proved effective in improving patients’ understanding of discomfort management following extubation. Conclusion: Education utilizing brochures and videos was effective in enhancing patients’ knowledge regarding the management of discomfort after extubation.